Female Representation in The Seventh-Grade English for Nusantara Textbook: A Critical Discourse Analysis - Pradana, Galih Rayi; Pramitha, Ayu Putri; Syahrizal, Trisnendri (IKIP Siliwangi, 2026)
Textbooks function as both language resources and cultural, ideological instruments that influence students' comprehension of gender identity. This study examines the representation of female characters in the English for Nusantara Grade VII textbook by Ika Lestari Damayanti et al. (2022) and how these depictions reflect underlying gender ideology. Textual and visual extracts were analyzed using Critical Discourse Analysis (Fairclough) combined with multimodal analysis (Kress & van Leeuwen) through three analytical phases: description, interpretation, and explanation. Research indicates that female characters are often portrayed in nurturing, supportive, and passive roles, encompassing caregiving, assistance, and generosity. Male figures, by comparison, seem more central and proactive in verbal and action-oriented episodes. Despite several visual depictions showcasing ladies as imaginative and self-assured, these empowering representations are statistically less prevalent. The textbook embodies commendable moral standards yet perpetuates nuanced gender inequality in role allocation. A more equitable representation is essential to foster healthy identity development for both male and female learners.